(untitled) (Terr@ Plural, 2019)
Our goal in this study was to analyze the amount and distribution of tree cover and green spaces in relation to urban zoning and census data of Rio Claro, SP, based on the integration between academic knowledge and the public authorities as an auxiliary tool in the planning and management of the urban forest. We found 11.88 km² of tree cover and 170 green areas within the urban perimeter. However, their spatial distribution is unbalanced once tree cover is concentrated in the city peripheries, while the green areas are concentrated in central areas. We propose alternatives to reduce the imbalance of tree cover and green areas between regions of the city. In the formulation of the current Master Plan, the active participation of undergraduate and graduate students in the creation and approval of amendments to the bill allowed the insertion of important elements for more sustainable management of the municipal landscape.